2015
DOI: 10.1186/s12871-015-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and use of labour analgesia among women at a low-income country antenatal clinic

Abstract: BackgroundChildbirth is one of the most painful experiences of a woman’s life. Authorities in the fields of obstetrics and anaesthesia encourage use of labour analgesia. Unlike in high-income countries, pain relief in labour in Africa is not a well established service, especially in the low-income countries like Uganda. Little is known about whether parturients would be amenable to labour analgesia. We sought to determine knowledge, attitudes and use of labour analgesia among women attending the antenatal clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2
21

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 12 publications
(13 reference statements)
3
38
2
21
Order By: Relevance
“…Various studies done in Nigeria on the level of awareness of labor analgesia reported 15-64% [4,5,10,16,18,19]. This is similar to what was reported from some other developing countries [11][12][13]15].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Various studies done in Nigeria on the level of awareness of labor analgesia reported 15-64% [4,5,10,16,18,19]. This is similar to what was reported from some other developing countries [11][12][13]15].…”
Section: Discussionsupporting
confidence: 76%
“…Studies on the level of awareness, perception, attitude and use of epidural analgesia for labor pain relief show that awareness and utilization of epidural labor analgesia is still very low in developing countries [6,7,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Another study stated that their participants knowledge about labour analgesia was obtained from friends, relatives, media and literature rather than from obstetricians. 18 Antenatal education of the women is important to sensitize them about pain relief in labour as women in developing country like India are generally subdued and their ability to seek and gain information is limited. Studies have also shown the benefit of integrating the services of anaesthetists, obstetricians and midwives both in educating the antenatal women and in providing labour analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, pain perception is subject to individual variations [19]. The large proportion of mothers not being sure whether they would demand labour analgesia might not be unrelated to the fact that many mothers in Africa are not even aware of the availability of such pain relief during child birth, unlike what is obtained in industrialized nations of the world [18,19,20]. A study in Uganda revealed that only 7% of women in that series had knowledge of obstetric anaesthesia, which mirrors the results of this study, where only 14.4% of mothers would demand obstetric anaesthesia [19].…”
Section: Discussionmentioning
confidence: 99%
“…Among the mothers who preferred vaginal delivery, 296 (67.6%) were not sure they would demand analgesia or anaesthesia to control labour pain, even though labour pain has been described by some authorities as extremely painful [18,19]. Nevertheless, pain perception is subject to individual variations [19].…”
Section: Discussionmentioning
confidence: 99%